Civil Law Transformation in the Digital Age: Challenges and Opportunities - Anggriani, Jum; Mukri, Moh; Jaya, Eni; Tarigan, Ester; Suprapti, Endang (ASAS, 2025)
Digital transformation has brought about fundamental changes in the Indonesian civil law system. This study aims to analyze the impacts, challenges, and opportunities of digital transformation in the context of civil law, as well as to formulate an ideal transformation model to accommodate the needs of the digital era. This study uses a normative legal research method with a qualitative approach based on literature studies and analysis of primary and secondary legal documents, including the application of sharia principles in digital transactions. One example of a case raised is the implementation of the murabahah contract in sharia e-commerce transactions that have not received explicit protection and recognition in the Civil Code, especially regarding the agreement clause and non-physical objects of sale and purchase such as digital assets. In practice, this sharia contract clause is often not accommodated by the conventional civil law structure, especially Article 1320 of the Civil Code concerning the valid conditions of an agreement and Article 1457 concerning sale and purchase. The results of the study indicate that digital transformation requires a reinterpretation of the basic concepts of civil law, the development of an adaptive regulatory framework, and the strengthening of digital infrastructure. The ideal legal transformation model should prioritize the principles of neutral technology and international harmonization, while maintaining the characteristics of the national legal system and the values ​​of sharia economic law. Key challenges include the digital divide, cybersecurity, and personal data protection, while opportunities include increasing the efficiency, accessibility, and transparency of the legal system. This study recommends developing a comprehensive regulatory framework, strengthening digital infrastructure, and increasing human resource capacity to support inclusive digital civil law transformation that is in line with sharia principles.